The problem of management of educational process in the creative university on the modern stage. (Journal of Educational Sciences, 2016)
In the article the peculiarities of the educational system for training creative personnel, who still remain out of sight during the development of regulations governing the activities of educational institutions of culture and art. For fast integration of the system of higher education into the international educational space it is necessary to increase responsibility for the quality of education each institution of higher education. This leads to changing approaches to managing educational organizations. The crisis in educational administration to a greater extent, in our opinion, are in the field of culture and art. One cannot ignore that the institution of art (specializing in musical, theatrical, visual and other arts) have a certain specificity. It is important that the accession to the Bologna process of musical education of the Republic has not lost its inherent consistency, continuity, professional thoroughness, practical orientation received by the students knowledge and skills and, as a consequence, the competitiveness in the international space.
Keywords: musical education; training creative personnel; integration; international education area; quality of education; Kazakhstan musical culture; the Conservatory; the Bologna process; competitiveness; master of the art